Irony Comprehension in Bidialectal Speakers - Antoniou, Kyriakos; Milaki, Emmanouela (My University, 2021)
Parallel to globalization, our world is becoming increasingly multilingual. We examined the effect of multilingualism on irony comprehension, focusing on a specific type of multilinguals, that is, bidialectal speakers of two dialects of the same language (Cypriot Greek and Standard Modern Greek). Specifically, we investigated the effects of second language (L2) proficiency and use on a continuous scale. We also examined the cognitive factors that underpin irony interpretation, focusing on executive control. Finally, we aimed to adjudicate between the direct and delayed access models of irony processing. We used an act-out test involving short videos, where irony was indexed by different (combinations of) cues (context, intonation, and face). Experiment 1 validated that ironic cues were perceived as such and were distinguishable from other comparable nonironic cues. Experiment 2 revealed that increased bidialectalism (specifically, higher L2 use) was associated with faster irony processing. Moreover, better working memory resulted in faster ironic interpretations. Finally, ironic interpretations were processed as fast as literal meanings, at least in some experimental conditions. The latter result supports the direct access model of irony. We discuss our findings in the context of 2 accounts of multilingual pragmatics—namely, that multilinguals enjoy a pragmatic advantage and that they have a monolingual-like pragmatic system.
Keywords: Multilingualism; Bidialectalism; Irony; Executive control; L2 use